Effect of mineral nutrients, seed treatment and foliar fungicides on spot blotch (Bipolaris sorokiniana) severity and agronomic performance of wheat (Triticum aestivum) in hot-humid environment of eastern Gangetic plain in India - GUPTA, ASHISH KUMAR; RAJ, RISHI; CHOUDHARY, R; SINGH, S P; SOLANKI, I S (The Indian Journal of Agricultural Sciences, 2017)
Spot blotch disease [Bipolaris sorokiniana (Sacc.)] is one of the most serious biotic constraint affecting wheat production in India. The effect of balanced macro- and micro-fertilization, fungicidal seed treatment and foliar fungicides either individually or in combination were assessed for their impact on spot blotch severity, grain yield, and other yield attributing characters during 2012-13 and 2013-14. Average maximum temperature (27.0°C) and high relative humidity (>90%) in February and March during both the years favoured disease development and spread. In vitro analysis of untreated pre-sown seeds using a blotter paper test revealed 19.2% and 32.5% seed infection with B. sorokiniana during 2012-13 and 2013-14, respectively. At the end of each cropping season, seed infection in harvested seed lots ranged from 5-6% in treatments with a combination of balanced fertility, seed treatment and foliar fungicide, 13% following two sprays of propiconazole, and 71% in control treatment. Application of balanced nutrition alone reduced AUDPC by 37% and increased grain yield up to 26%. However, the combined influence of balanced nutrition, carboxin + thiram seed treatment and two foliar sprays of propiconazole resulted in a 99% reduction in AUDPC values with 60% higher grain yield (6.30 t/ha), 45% higher TKW (41.33 g) and significant increase in other yield attributes. The current study illustrates the role of a combination of crop and disease management practices in the control of spot blotch and improving the agronomic performance of wheat in eastern plains of India.